2014
DOI: 10.1002/esp.3662
|View full text |Cite
|
Sign up to set email alerts
|

A multi‐dimensional analysis of pro‐glacial landscape change at Sólheimajökull, southern Iceland

Abstract: Pro‐glacial landscapes are some of the most active on Earth. Previous studies of pro‐glacial landscape change have often been restricted to considering either sedimentological, geomorphological or topographic parameters in isolation and are often mono‐dimensional. This study utilized field surveys and digital elevation model (DEM) analyses to quantify planform, elevation and volumetric pro‐glacial landscape change at Sólheimajökull in southern Iceland for multiple time periods spanning from 1960 to 2010. As ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 59 publications
1
62
0
Order By: Relevance
“…Use of existing 'stable' features for ground control is a limitation of studies that use photogrammetric methods to produce DEMs of changing geomorphological systems (e.g. Schiefer and Gilbert, 2007;Staines et al, 2015), and means it is rarely possible to achieve an optimal distribution of GCPs (ground control points).…”
Section: Evaluation Of Dem Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…Use of existing 'stable' features for ground control is a limitation of studies that use photogrammetric methods to produce DEMs of changing geomorphological systems (e.g. Schiefer and Gilbert, 2007;Staines et al, 2015), and means it is rarely possible to achieve an optimal distribution of GCPs (ground control points).…”
Section: Evaluation Of Dem Qualitymentioning
confidence: 99%
“…For additional validation, randomly generated spot heights (n = 4370) from more geomorphologically 'stable' areas (e.g. Staines et al, 2015) (Fig. 3A).…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Sedimentological characterization of the moraine basin by Westoby et al (2015) revealed low median surface grain sizes toward the rear of the basin, which may be indicative of a longer sediment exposure time for, or preferential exposure to, in situ weathering relative to the remainder of the site, leading to the comminution of surficial deposits and the enhancement of sub-debris ice ablation, which promotes terrain relaxation (e.g. Krüger and Kjaer, 2000;Schomacker, 2008;Irvine-Fynn et al, 2011;Staines et al, 2015).…”
Section: Implications For Glaciological Process Analysismentioning
confidence: 99%
“…Baltsavias et al, 2001;Pitkänen and Kajuutti, 2004;Keutterling and Thomas, 2006;Schwalbe and Maas, 2009;Immerzeel et al, 2014;Pepin et al, 2014;Whitehead et al, 2014;Gabbud et al, 2015;Kraaijenbrink et al, 2016;Piermattei et al, 2015;Ryan et al, 2015;Kääb et al, 2014); mapping the redistribution of proglacial sediment (e.g. Milan et al, 2007;IrvineFynn et al, 2011;Dunning et al, 2013;Staines et al, 2015) and moraine development ; the characterization of glacier surface roughness (e.g. Sanz-Ablanedo et al, 2012;Irvine-Fynn et al, 2014), glacial sedimentology (Westoby et al, 2015) and hydrology (Rippin et al, 2015) as well as input data for surface energy balance modelling (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Eiken and Sund, 2012), although it is relatively time-consuming (restricting the number of features processed) and is unlikely to deliver sub-pixel accuracies. This is (Staines and others, 2015). In (b), the box indicates the surveyed region shown in Figure 8a, with the black circle giving the location of the TLS and time-lapse camera.…”
Section: Glacier Feature Trackingmentioning
confidence: 99%